A STUDY ON AQUAPONIC CULTIVATION OF VANNAMEI SHRIMP (Litopenaeus vannamei) AND WATER SPINACH (Ipomoea aquatica Forsk) UNDER LOW SALINITY - Fahrur, Mat; Dharmawan Trijuno, Dody; Zainuddin, Zainuddin; Chaidir Undu, Muh; Makmur, Makmur; Taukhid, Imam; Syah, Rachman (Indonesian Aquaculture Journal, 2024)
Cultivation waste poses a severe threat to reducing environmental quality. However, the problem of low salinity cultivation waste can be overcome by converting it into plants. This research was conducted to assess the impact of salinity on the growth performance of Vannamei shrimp (Litopenaeus vannamei) and water spinach (Ipomoea aquatic Forsk) in a low-salinity aquaponic system. Floating raft system for planting water spinach. Furthermore, the role of water spinach in using N and P nutrients from the culture media of vannamei shrimp was analyzed. The experiment was carried out for 35 days, with two treatments and three repetitions, namely 5 and 10 ppt. Salinity affected the growth performance of shrimp and water spinach. Shrimp reared at 10 ppt exhibited higher growth rate, harvest size, and shrimp yield, along with lower feed conversion ratio (FCR) and water use compared to those reared at 5 ppt. Meanwhile, the performance of water spinach at 5 ppt salinity resulted in higher survival, plant height gain, root length gain, number of leaves, and yield of water spinach compared to 10 ppt salinity. The growth performance of water spinach decreased with increasing salinity, and the efficiency in reducing N and P from the 5 ppt culture media was 1.3 times higher than that of 10 ppt. Water spinach showed better results in the 5 ppt salinity media than 10 ppt, while vannamei shrimp grew at 5 ppt. Therefore, 5 ppt salinity was recommended as a suitable condition for integrated cultivation of vannamei shrimp and water spinach in low-salinity aquaponics. Both species were compatible and complemented each other’s role in developing low-salinity aquaponics.